Talent management survey - Kumar, Vikas (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Talent points to the ability to learn and evolve in the light of new challenges. Talent is about potential from the past, not about past performance. Talent tends to take risks and be willing to learn from mistakes, measured in terms of having certain traits, such as reasonable (but not so high) ability to focus on the level of ambition and competitiveness, issues' big picture '. Awareness of your strengths, limitations and influences on others. Different talent management processes must be on a strategic level to be successful. These processes /strategies include talent validation, recruitment and evaluation, competency management, performance management, career development, learning management, compensation and succession planning. Keywords: Tourism, SME’s, Dual Economic Structure, Travel Agency, Retail Tourism Production.